SELF-EFFICACY AND SPEAKING PERFORMANCE: A CORRELATIONAL STUDY AT TWELFTH-GRADE SENIOR HIGH SCHOOL STUDENTS - Shinta Sopia, Cika; Yulianto, Slamet Wahyudi (ReALL - Research on Applied Linguistics and Literature, 2023)
The purpose of this study is to determine the relationship between self-efficacy and students' speaking performance. In terms of literal awareness, dealing with main ideas and supporting details in the first semester of twelfth grade for senior high school students in the academic year 2023/2024. The researcher employs a correlational study as a research design to explain the correlation. The population is students from the XII MIPA 2 semester. A total sampling of students from each class is conducted, so that 32 people are obtained as the sample for this research. Questionnaires and speaking test interviews are used by researchers in gathering data. The researcher utilized SPSS to examine and calculate the connection. The correlation level was discovered to be 0.805, indicating a high positive association between both. The findings of this study show a significant association between students' self-efficacy in speaking performance and literal understanding. It is recommended that teachers consider these findings when carrying out activities in class with varied student characteristics.